Nonaudit services purchases, audit committee effectiveness and investment opportunity set. - Goh, Yee Chung. (2008)
This study examines the extent to which effective audit committees limit the level of nonaudit services purchased from the firms’ external auditors. We hypothesize that thenegative association between audit committee effectiveness and nonaudit services purchases is moderated by the investment opportunity set of the firm.